Experimental characterization of particle-wall interaction relevant to entrained-flow gasification of biomass. (1st December 2017) - Troiano, Maurizio; Montagnaro, Fabio; Salatino, Piero; Solimene, Roberto
Highlights: Particle-wall interactions were characterized by impact experiments. Char with different carbon conversion and ash particles of two biomasses were used. Experimental tests were carried out in cold and hot conditions. Global restitution coefficient of char decreased with temperature from 0.4 to 0.3. Ash deposition efficiency was around 0.3 for wood chips and 0.8 for corn stover. Abstract: The present study addresses particle–wall interaction phenomena relevant to entrained-flow gasifiers. Two types of biomass have been investigated, i.e. wood chips and corn stover. The dynamics of char and ash particles as they are impacted onto a flat surface in cold and hot conditions has been characterized by means of high speed imaging and tracking. Particle–wall collisions were described in terms of normal, tangential and global coefficients of restitution as well as deposition efficiency. The influence of carbon conversion and impact velocity on the dynamical pattern of rebound and deposition has been investigated. The results indicate that, even at ambient conditions, some plastic deformation occurs during the impact. Experiments performed under hot conditions demonstrate that a drop of the coefficients of restitution takes place at high temperature, especially at low impact velocity, for both the tested biomasses. This feature can be explained by considering the change of mechanical properties of particles as the temperature increases, and the effect of the adhesion energy during the impact. Results highlighted that ash of wood chips is not prone to form a slag layer, while ash of corn stover extensively contributes to formation of ash deposits and melts under hot conditions. Results from experiments with corn stover indicate that char particles deposit onto the molten ash surface. The dissipation of momentum associated with particle impact promotes the establishment of a dense-dispersed phase in the near-wall zone of entrained-flow slagging gasifiers.